Cartografia do acolhimento ao acadêmico em sofrimento psíquico nas universidades públicas brasileiras - RODRIGUES, Kevin Christian do Carmo (2020)
University life demands stressful conditions. During this period there may be situations of accidental seizures arising from various factors, generating emotional imbalance. This study is a documentary research presented as cartography aiming to map the psychosocial support services to the academic in psychological distress, identifying specifically the types of services offered and the way of access to them. Data were collected from August to October 2019 on e-MEC and on the websites of Brazilian public universities. There were 108 existing public universities in Brazil, of which 107 were considered for the study. More than half, 68% (73), report on their websites offering mental health care services. Only 57.5% (42) of these 73 universities describe the type of service offered. The services reported by these universities were divided into four groups: Psychological duty - offered by 24.3% (26) of the study universities, Integrative and Complementary Practices and group activities - offered by 17.75% (19), Brief Psychotherapy - offered by 13.08% (14) and Prevention Activities - offered by 5.6% (6). Regarding how students are given access to services, 58.9% (43) provide this information. Considering the total number of universities (107), 26.16% (28) attend by scheduling, 13.08% (14) through spontaneous demand and 0.93% (1) attend by scheduling and spontaneous demand. It is concluded that mental health care services exclusive to university students - offered by universities - besides being mandatory, are essential for the maintenance of mental health and cure of psychological distress. It was found that the lack of information on how access is provided and the types of services offered is a factor that hinders the insertion of students in the service, weakening the reception of university students. Universities should facilitate access to information about the services offered and implement prevention activities.